Formulation of Quality Assurance Social Indicators in Community Forest Health Assessment - Irwan Sukri Banuwa; Wahyu Hidayat; Rudi Hilmanto; Rommy Qurniati; Rahmat Safe’i (Journal of Sylva Indonesiana, 2024)
Community forests provide benefits to their functions and roles in meeting community needs and environmental sustainability based on economic, social, and ecological perspectives. Social indicators play this role in the sustainability of community forest health. This study aims to obtain a weighted value (quality assurance) of social indicators in assessing the health of community forests. The stages of research carried out included, among others, conducting interviews with questionnaire instruments with respondents, determining the priority scale with the Analytic Hierarchy Process (AHP) method, and determining eigenvalues with the Analytic Networking Process (ANP) method. Based on the results of the study, four social indicators can describe the health condition of community forests: education indicators, employment indicators, participation indicators, and institutional indicators. These indicators have the same level of importance, where the eigenvalues obtained do not have significant differences. It means that community forest farmers have realized that social indicators can support environmental sustainability in aspects of forest health. Thus, the weighted values obtained by social indicators from the highest to the lowest are indicator participation (0.29), education indicator (0.27), institutional indicator (0.23), and employment indicator (0.21). The formation of farmer groups needs to be done to improve local institutions. Therefore, they can support community forest management regulations